Rediscovery of PHI-1/PPP1R14B: Emerging Roles of Cellular PP1 Signaling Mediated by the PPP1R14B Gene Product in Multiple Cancers and Beyond - Masumi Eto (Biomolecules)
PHI-1, encoded by PPP1R14B, regulates cellular protein phosphatase-1 (PP1) signaling and has emerged as both a biomarker and therapeutic target. Initially identified as a phospholipase-neighboring gene (PNG), PHI-1 is now known for its phosphorylation-dependent inhibition of PP1 holoenzymes, with bi-directional roles depending on its expression levels. Under physiological conditions, PHI-1 selectively regulates PP1 activity to maintain cellular homeostasis, whereas its pathological upregulation promotes oncogenic pathways, stabilizes tumor-promoting proteins, and modulates immune responses. This article explores PHI-1’s emerging role as a pan-cancer biomarker in parallel with emphasizing its physiological functions in signaling networks, smooth muscle contraction, cytoskeletal dynamics, and selective proteostasis. The mechanistic insights highlight PHI-1’s potential in precision oncology, offering opportunities for developing diagnostics and therapies that target its conditional functions.